RADIKAL DULU, TERORIS KEMUDIAN: GERAKAN ISLAM “GARIS KERAS” DULU DAN KINI DALAM TINJAUAN SOSIO-HISTORIS - Syaepu, Indra Latif (STAIN Kediri, 2017)
This paper analyzes the phenomenon of radicalism and analysis of the terminology of terrorism in Islam. Radicalism is a movement carried out by individuals or groups who are plagued by socio-political and sociohistorical phenomena. The symptoms of violent practice perpetrated by a group of Muslims, historically - sociologically, more appropriately as socio-political phenomena than religious phenomena even with the rise of religious banners.Radicalism and terrorism are of course different. In democracy, as long as there is no violence, legal radicalism is lawful. While terrorist acts, inherent in doing their shortcomings by acts of violence are haram. But radicalism is linked to terrorism in some ways. Keywords: Radicalism, terorism, history, socio-historical